MULTICULTURAL VALUES IN THE CONCEPT OF ISLAMIC BROTHERHOOD: A Study from the Hadith Perspective - Rosyidin, Muhammad Abror; Khoir, Qoidul; Damanhuri, Damanhuri; Fikri, Abdillah Dzul (LP2M Ma'had Aly Hasyim Asy'ari Pesantren Tebuireng, 2025)
This study examines the multicultural values conveyed by the Prophet Muhammad (peace be upon him) in Hadith al-BukhÄrÄ« No. 6065. The tendency to harm and hate one another in this era of openness threatens Islamic brotherhood, making this study essential to reaffirm the teachings of Rasulullah SAW on harmony and multiculturalism. The research focuses on four main aspects: (1) the analysis of the hadithâ€™s authenticity, (2) the jurisprudential (fiqh) analysis of the hadith, (3) the correlation of Hadith al-BukhÄrÄ« 6065 with the Qurâ€™an and other hadiths, and (4) the multicultural values embedded within the hadith. This study adopts a qualitative approach using library research methods by consulting relevant literature and documents. The findings of this study are as follows: (1) no defects, instances of tadlÄ«s, or other weaknesses were found in either the matn (text) or isnÄd (chain of transmission) of Hadith al-BukhÄrÄ« 6065; (2) the hadith aligns with Qurâ€™anic verses such as al-á¸¤ujurÄt [49]:10 and Ä€li â€˜ImrÄn [3]:103, as well as with other hadiths (á¹¢aá¸¥Ä«á¸¥ al-BukhÄrÄ« 6076 and 6064; 6 narrations from á¹¢aá¸¥Ä«á¸¥ Muslim 2641; Sunan AbÄ« DÄwÅ«d 4910; JÄmi' at-TirmidhÄ« 1935/Sunan at-TirmidhÄ« 2039; al-Muwaá¹á¹aâ€™ 2639 and 2640; and Musnad Aá¸¥mad 12073, 12691, 13053, 13179, 13180, 13354, 13935, and 14016); (3) Hadith al-BukhÄrÄ« 6065 conveys three key messages: (a) prohibition of tadÄbur (turning away from one another), tabÄguá¸ (mutual hatred), and taá¸¥Äsud (envy); (b) command to foster brotherhood; and (c) prohibition of al-á¸¥ajr (shunning others); and (4) the multicultural values contained in the hadith include spiritual-religious values, the universality of brotherhood, harmony between theoretical and practical paradigms, and socio-spiritual balance. [Penelitian ini membahas nilai-nilai multikultural yang dipesankan Rasulullah SAW dalam hadis al-BukhÄrÄ« nomor 6065. Perilaku saling menyakiti dan membenci di era keterbukaan berpotensi merusak persaudaraan umat Islam, sehingga kajian ini penting untuk menegaskan ajaran Rasulullah SAW tentang harmoni dan multikulturalisme. Penelitian ini fokus pada (1) analisis kualitas hadis; (2) analisis fikih hadis; (3) korelasi hadis al-BukhÄrÄ« 6065 dengan Al-Qurâ€™an dan hadis-hadis lain; serta (4) nilai-nilai multikultural yang terkandung di dalam hadis al-BukhÄrÄ« 6065. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi pustaka dari literatur dan dokumen yang berkaitan dengan tema penelitian. Hasil penelitian ini adalah (1) tidak ditemukan kecacatan, ke-tadlÄ«s-an, maupun unsur-unsur kelemahan lain dari matan maupun sanad hadis al-BukhÄrÄ« 6065; (2) hadis al-BukhÄrÄ« 6065 sejalan dengan ayat 10 al-á¸¤ujurÄt, ayat 103 Ä€li â€˜ImrÄn, dan hadis-hadis lain (á¹¢ahÄ«h al-BukhÄrÄ« 6076 dan 6064, 6 riwayat á¹¢ahÄ«h Muslim 2641, Sunan AbÄ« DÄud 4910, JÄmiâ€™ at-TirmiÅ¼Ä« 1935/Sunan at-TirmiÅ¼Ä« 2039, Muwaá¹á¹aâ€™ 2639 dan 2640, serta Musnad Aá¸¥mad 12073, 12691, 13053, 13179, 13180, 13354, 13935, dan 14016); (3) hadis al-BukhÄrÄ« 6065 memiliki 3 pesan utama, yaitu (a) larangan berbuat tadÄbur (saling memalingkan diri), tabÄguá¸ (saling membenci), dan taá¸¥Äsud (saling dengki), (b) perintah untuk menjalin persaudaraan, dan (c) larangan melakukan al-á¸¥ajr; serta (4) nilai-nilai multikultural yang terkandung adalah nilai spiritual-religius, universalitas persaudaraan, nilai keselarasan paradigma antara teori dan praktik, dan nilai keseimbangan sosio-spiritual.]